2021
DOI: 10.1186/s12920-021-01050-6
|View full text |Cite
|
Sign up to set email alerts
|

Mediation role of body fat distribution (FD) on the relationship between CAV1 rs3807992 polymorphism and metabolic syndrome in overweight and obese women

Abstract: Background Metabolic syndrome (MetS) is associated with an increased risk of morbidity and mortality in almost all chronic diseases. The most frequent methods for the calculation of a continuous MetS (cMetS) score have used the standardized residuals in linear regression (z-score). Recently, emerging data suggest that one of the main genetic targets is the CAV1, which plays a crucial role in regulating body fat distribution. This study is designed to investigate the relationship between CAV1 rs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Little is known about CAV1 regulation in adipocytes; single nucleotide polymorphisms (SNPs) in the CAV1 gene have been associated with metabolic syndrome (MetS), which is a major risk factor for diabetes and coronary artery disease. Several CAV1 SNPs were found to be associated with MetS, including rs926198 in Caucasians and Hispanics [ 11 ], rs3807989 in Han Chinese [ 12 ], rs11773845 in Latin Americans [ 13 ], rs3807992 in Persians [ 14 ], and rs1997623 in Kuwaiti children, as shown in our previous study [ 15 ], and as found in another adult population [ 16 ]. Although central obesity is a landmark trait for the diagnosis of MetS, the full spectrum of traits relating to MetS includes various other metabolic factors related to hypertension, diabetes, and dyslipidemia.…”
Section: Introductionsupporting
confidence: 68%
“…Little is known about CAV1 regulation in adipocytes; single nucleotide polymorphisms (SNPs) in the CAV1 gene have been associated with metabolic syndrome (MetS), which is a major risk factor for diabetes and coronary artery disease. Several CAV1 SNPs were found to be associated with MetS, including rs926198 in Caucasians and Hispanics [ 11 ], rs3807989 in Han Chinese [ 12 ], rs11773845 in Latin Americans [ 13 ], rs3807992 in Persians [ 14 ], and rs1997623 in Kuwaiti children, as shown in our previous study [ 15 ], and as found in another adult population [ 16 ]. Although central obesity is a landmark trait for the diagnosis of MetS, the full spectrum of traits relating to MetS includes various other metabolic factors related to hypertension, diabetes, and dyslipidemia.…”
Section: Introductionsupporting
confidence: 68%
“…VIM (vimentin) binds to insulin-responsive aminopeptidas, a major cargo protein of glucose transporter type 4, and decreases the glucose tolerance [ 182 ]. IFI16 [ 193 ], ERBB2 [ 194 ], VIM (vimentin) [ 182 , 195 ] and CAV1 [ 160 , 196 , 197 , 198 , 199 ] are crucial factors for advancement of obesity. IFI16 showed adipogenesis, an enhanced inflammatory state and damaged insulin-stimulated glucose uptake in adipose tissue [ 193 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some possible functional roles for CAV-1 may be inherited. CAV-1 has also been shown to have a key regulatory function in fat distribution and genetic lipodystrophy in humans (40).A cross-sectional study has reported that processed meat consumption (6.8 g/d) compared to white meat/poultry is more likely to be associated with central obesity (15). In a study, Halkjaer et al showed that a diet rich in processed meat predicts high level of WC among 89 432 men and women from ve countries participating in European Prospective Investigation into Cancer and Nutrition (EPIC) (41).…”
Section: Discussionmentioning
confidence: 99%